Medical Governance: Are We Ready to Prescribe? - Weimer, David L. (My University, 2006)
Federal and state governments in the United States play substantial and complex roles in promoting, subsidizing, regulating, and even providing health care in the United States. Financial pressures on Medicare and Medicaid, concerns about the translation of evidence-based findings into medical practice, and efforts to reduce the number of people without any health insurance are likely to expand governments? roles even further in the future. Although a large body of research seeks ways to improve the delivery of medical services, relatively little research addresses the advantages and disadvantages of the various governance arrangements that are or could be used to make better collective decisions about the allocation of medical resources. Assessments of the many types of governance arrangements already employed ? advisory committees such as those employed by the Food and Drug Administration, menu-creating commissions with narrow mandates such as the Oregon Health Plan, and stakeholders trusteeships such as the Organ Procurement and Transplantation Network ? should be an important topic for health policy research pursued by public policy and management scholars. Absent these efforts, the policy community may not be able to offer good advice about medical governance.